Pengetahuan Keluarga Pasien tentang Triase dengan Kepuasan Keluarga Pasien dalam Pelayanan Keperawatan - Sukrang Sukrang; Hasnidar Hasnidar; Fauzan Fauzan (Syntax Idea)
Emergency Unit is one of Hospital unit that providing the treatment toward patient based on triage, but in fact not all the patient’s family understanding well regarding it and then they though have negligence when reach in Emergency Unit. The aim of research to analyses the association of knowledge of patient’s family about triage with satisfaction of patient’s family in nursing care in emergency unit of Undata Hospital, Central Sulawesi Province. This is quantitative research with correlation method and cross sectional approached. The population of research is those patient’s family who visiting to Emergency Unit and total of sampling is 73 respondents that taken by purposive sampling technique. Data analysed by chi-square test with knowledge of patient’s family about triage as an independent variable and satisfaction of patient’s family in nursing care as a dependent variable. The result of research shown that about 50,7% have less knowledge. Bivariate analyses result by chi-square test found that have association of knowledge of patient’s family about triage with satisfaction of patient’s family in nursing care with p value (p≤α) = 0,00≤0,05. Conclusion mentioned that have association of knowledge of patient’s family about triage with satisfaction of patient’s family in nursing care in emergency unit of Undata Hospital, Central Sulawesi Province.